SELF REPORTED OF HEALTH LITERACY, PHYSICAL ACTIVITY AND SLEEP QUALITY: A CORRELATION ANALYSIS AMONG ELDERLY PATIENT AT PUBLIC HEALTH CENTER - Defi Wulan Rachmawati; Indra Himawan Susanto; Ananda Perwira Bakti; Yetty Septiani Mustar; Muhammad Arja Bahauddin (Universitas Hamzanwadi, 2026)
Decreased physical activity and sleep disorders are common problems among older adults. Health literacy is thought to play a role in motivating healthy behaviors, but its relationship with physical activity and sleep quality among older adults in Indonesia has been little studied. The purpose of this study was to analyze the correlation between health literacy, physical activity, and sleep quality among older adults at a community health center. This study used a quantitative cross-sectional research method with 35 elderly respondents aged ≥ 65 years at the Lidah Kulon Community Health Center. Sampling was conducted using accidental sampling. Data were collected through guided interviews using the HLS-EU-Q16 health literacy, PASE physical activity, and PSQI sleep quality questionnaires. Data analysis used the Spearman Rank correlation test. The results of this study showed that most respondents were female 65.7% and aged 66-74 years 62.9%. No significant relationship was found between health literacy and physical activity (r=0.054; p=0.760) or sleep quality (r=-0.187; p=0.280). However, a strong and significant negative relationship was found between physical activity and sleep quality (r=-0.721; p=0.000). The conclusion of this study is that health literacy is not directly correlated with physical activity or sleep quality among the elderly at this health center.